The interaction between captured human thrombin and antithrombin studied by surface plasmon resonance, and the effect of melagatran. Issue 3 (2002) - Elg Elg, Susanne Susanne; Deinum Deinum, Johanna Johanna
Abstract : The kinetics of the interactions between thrombin and antithrombin were studied by surface plasmon resonance. Although amine coupled thrombin binds low molecular weight active site inhibitors with a one-to-one stoichiometry hirudin only bound to 75% of the coupled active thrombin. However, antithrombin or thrombomodulin could not bind at all to amine-coupled thrombin. To make it possible to follow the reaction with antithrombin in time thrombin was therefore captured on an antibody against thrombin. Alternatively, antithrombin was captured on an antibody against antithrombin to follow complex formation with thrombin. With these techniques the second-order rate constant for the interaction of antithrombin with thrombin in the presence of heparin, was estimated to be ka ≥0.4×10 6 M −1 s −1 with K D ═ 50 nM for the formation of the initial complex. These values are similar to those found in solution. In the absence of heparin, the second-order rate constant for the interaction of thrombin with captured antithrombin was only k a ═ 9×10 3 M −1 s −1 . Thus, with this technique rate constants for the interaction of proteases with serpins can be determined in a convenient way, without the need for stopped-flow. The rapid‒binding, active-site-directed thrombin inhibitor, melagatran, competed with the antithrombin-thrombin interaction. Although melagatran, a reversible thrombin inhibitor, initially prevented formation of the complex, ultimately the irreversible thrombin-antithrombin complex was always formed.